Microbiological Study of Yamal Lakes: A Key to Understanding the Evolution of Gas Emission Craters - Alexander Savvichev; Marina Leibman; Vitaly Kadnikov; Anna Kallistova; Nikolai Pimenov; Nikolai Ravin; Yury Dvornikov; Artem Khomutov (Geosciences, 2018)
Although gas emission craters (GECs) are actively investigated, the question of which landforms result from GECs remains open. The evolution of GECs includes the filling of deep hollows with atmospheric precipitation and deposits from their retreating walls, so that the final stage of gas emission crater (GEC) lake development does not differ from that of any other lakes. Microbial activity and diversity may be indicators that make it possible to distinguish GEC lakes from other exogenous lakes. This work aimed at a comparison of the activity and diversity of microbial communities in young GEC lakes and mature background lakes of Central Yamal by using a radiotracer analysis and high-throughput sequencing of the 16S rRNA genes. The radiotracer analysis revealed slow-flowing microbial processes as expected for the cold climate of the study area. GEC lakes differed from background ones by slow rates of anaerobic processes (methanogenesis, sulfate reduction) as well as by a low abundance and diversity of methanogens. Other methane cycle micro-organisms (aerobic and anaerobic methanotrophs) were similar in all studied lakes and represented by Methylobacter and ANME 2d; the rates of methane oxidation were also similar. Actinobacteria, Bacteroidetes, Betaproteobacteria, and Acidobacteria were predominant in both lake types. Thus, GEC lakes may be identified by their scarce methanogenic population.